Composite action of the track slab and the self-compacting concrete filling layer subjected to train-induced fatigue load: An experimental investigation. (May 2019) - Liu, Xiaochun; Yu, Zhiwu; Xiang, Ping; Jin, Cheng
To investigate the composite performance of the track slab and the self-compacting concrete filling layer in the China Railway Track System III slab track structure, six segmental specimens comprising either one or a pair of sleepers were fabricated by dividing a full-scale slab track structure. Fatigue tests in the transverse bending perpendicular to the rail were conducted on four slab track specimens supported on rubber plates simulating the subgrade, to a maximum of five million applied load cycles. It was observed in the fatigue tests that longitudinal cracks first appeared on the top surface of the track slab at the mid-span of the specimen. Splitting cracks appeared later from the anchorage ends of the transverse prestressed tendons to the top surface of track slab. Delamination of the track slab–filling layer interface developed with increasing number of cycles. Static three-point bending tests were also conducted on both fatigue-damaged and control composite plate specimens to evaluate the effect of fatigue damage on the composite performance of the track slab and the filling layer. In the static tests, significant deformation developed in the fatigue-damaged specimens from the start of loading, and the fatigue damage and interface delamination adversely affected the composite action of the track slab and the filling layer. Static loads corresponding to new cracking of the fatigue-damaged composite plates were reduced by 20–30%, and the load corresponding to the initial interlayer slip reduced by 25–62% compared with the control specimens. The interfacial bond strength between the track slab and the filling layer is the first line of defense against the interlayer slip, and the dowel action of the interlayer connection reinforcement is the second line of defense. Roughening by multitooth chiseling on the track slab and an increase in the ratio of interlayer connection reinforcements are both effective ways to enhance the composite action of the track slab and the filling layer.